Incidence and Associated Factors of Postoperative Pulmonary Complications after Abdominal Surgery in the Public Hospital, Addis Ababa, Ethiopia - Geresu Gebeyehu; Ashenafi Eshetu; Senait Aweke (Anesthesiology Research and Practice)
Background. Postoperative pulmonary complications are a wide variety of disorders that affect normal respiratory functions, which in turn lead to morbidity and mortality. The extent to which it occurs is not yet studied in most clinical settings. This study assessed the incidence and risk factors of postoperative pulmonary complications in patients undergoing abdominal surgery under general anesthesia. Methods. A multicenter, prospective cross-sectional study was conducted at Menelik II, Tikur Anbessa Specialized, Zewditu Memorial, and Yekatit 12 Memorial hospitals after obtaining ethical clearance from each hospital. The study recruited a total of 287 participants using systematic random sampling. The data collection tool included sociodemographic, surgical, and anesthetic factors. Participants were followed for 7 days postoperatively, and any respiratory problems were recorded once identified. The collected data were entered and analyzed using SPSS version 26. Both bivariate and multivariate logistic regressions were used for analysis. A p value of <0.05 was considered statistically significant. Results. About 33% of the participants that underwent abdominal surgery developed postoperative pulmonary complications. Age > 65 years (AOR = 12.091, 95% CI = 3.310–44.169), duration of surgery >3 hours (AOR = 11.737, 95% CI = 3.621–38.039), preoperative oxygen saturation <94% (AOR = 10.671, 95% CI = 3.794–30.016), and postoperative serum albumin level <3.5 g/dl (p value <0.001) were associated with postoperative pulmonary complications significantly. Conclusion and Recommendations. The incidence of postoperative pulmonary complications after abdominal surgeries was high. Age >65years, duration of surgery >3 hours, preoperative SpO2% <94%, cigarette smoking, and postoperative serum albumin level <3.5 g/dl were factors strongly associated with postoperative pulmonary complications. We recommend special care for elderly patients, limit the surgical duration to less than 3 hours, treat the underlying cause of desaturation, and correct postoperative serum albumin to prevent the occurrence of postoperative pulmonary complications.